Peningkatkan Derajat Kesehatan Masyarakat Desa melalui Penguatan Kader dan Edukasi Penyakit Tidak Menular Berbasis Kuliah Kerja Nyata - hendrarif; Susanti; Evy Apriani; Dwi Setiyawati; Kasron; Ahmad Kusnaeni; Ahmad Subandi; Suko Pranowo (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2025)
Non-Communicable Diseases (NCDs), such as hypertension and diabetes mellitus (DM), remain major public health issues, including in rural areas. This community engagement activity aimed to improve the health status of residents in Tanjung Baru Village through education and empowerment of local health cadres in NCD prevention. The method used was a participatory-educational approach implemented through a community service program (KKN) from June 10 to 23, 2025. Interventions included health education, blood pressure and blood glucose screening, cadre training, hypertension exercise sessions, herbal remedy preparation, and waste bin recycling. The results showed significant improvements: the number of residents who understood NCD symptoms increased from 35 to 132, participants in health screening rose from 28 to 118, and active cadre involvement increased from 5 to 12. The program also enhanced participation in physical activities, hygiene education, and residents’ commitment to early detection. In conclusion, educational and collaborative approaches in community-based programs proved effective in improving health literacy and local capacity for NCD prevention.